ANALISIS BIAYA DAN PENDAPATAN USAHATANI CABAI RAWIT DI KECAMATAN CIGALONTANG KABUPATEN TASIKMALAYA - Anisa Puspitasari (Universitas Galuh Ciamis, 2020)
Chili is one of the leading national vegetable commodities and has quite high economic value. The need for red cayenne pepper continues to increase every year in line with the increasing population and the development of industries that need raw cayenne pepper. The purpose of this study is to analyze the cost, income and efficiency of cayenne pepper farming in Cigalontang District. Research respondents were 30 farmers. The results showed the revenue of cayenne pepper farming in Cigalontang Subdistrict amounted to Rp 130,733,510/ha/year, cash costs Rp 69,582,450/ha/year, and a total cost of Rp 73,765,150. The cayenne pepper farming is advantageous from the income of Rp 61,151,060. The efficiency of cayenne farming from cash costs is 1.88 and from a total cost of 1.77.